Synthesis of 4-Hydroxycinnamic Acid from Malonic Acid and 4-Hydroxybenzaldehyde as Starting Materials with the Variation of the Reflux Time - Narwanti, Iin; Abdillah, Fahmi Humaidi (Borneo Journal of Pharmacy, 2026)
Cinnamic acid derivatives, naturally occurring compounds found in plants and also synthetically produced, exhibit diverse biological activities, including antioxidant, antiplasmodial, tyrosinase-inhibitory, antibacterial, anti-inflammatory, antitumor, and anticancer properties, with 4-hydroxycinnamic acid representing a particularly valuable derivative for pharmaceutical development. However, the successful synthesis of these compounds requires careful optimization of reaction conditions, particularly the reflux time, which must balance complete reactant conversion against product degradation that may occur with excessive heating to achieve maximum yield and purity. This study aimed to optimize the reaction yield in the synthesis of 4-hydroxycinnamic acid by varying the reflux time. 4-Hydroxycinnamic acid was synthesized via a reaction between malonic acid and 4-hydroxybenzaldehyde using pyridine-piperidine as a catalyst. The reflux time was varied at 3, 5, and 7 hours. The mixture was refluxed at 70–80°C with constant stirring at 900 rpm. After the reaction, the crude product was recrystallized and dried, and the yield was calculated. TLC was employed to compare the product's Rf value with that of the starting material using various eluents. Furthermore, the synthesized product was characterized by Fourier-Transform Infrared and Nuclear Magnetic Resonance spectroscopy to elucidate its structure. The results revealed that the average yields at reflux times of 3, 5, and 7 hours were 58.6, 66.78, and 63.87%, respectively, with the optimal yield achieved at 5 hours. Physicochemical and spectral data confirmed that the obtained product was 4-hydroxycinnamic acid. Purity analysis showed that the synthesized compound had a purity level of 95%.